Pengembangan Desa Wisata Berbasis Masyarakat (Community Based Tourism) terhadap Ekonomi Masyarakat di Desa Kembang Kuning Kabupaten Lombok Timur - Chika Marshendalia; Prayitno Basuki; Irwan Suriadi (Lembaga Pengembangan Kinerja Dosen, 2026)
The main objective of this study is to examine how the Kembang Kuning Community-Based Tourism Village was formed and how it contributes to the local economy. Specifically, this study explores how the development of the tourism village affected the socioeconomic status of the community both before and after its formation, how the principles of Community-Based Tourism were integrated into destination management, and how tourism development helped local residents earn more income and find better jobs. A qualitative approach utilizing descriptive methodology was employed in this study. Documentation, in-depth interviews, and field observations were used to collect data. Triangulation of sources, methodologies, and theories was used to assess the validity of the data. According to the research results, the majority of the village's residents earned their living through subsistence farming before the hamlet became a tourist attraction. The implementation of Community-Based Tourism was carried out through direct community involvement in program planning, tourism management, homestay facilities provision, MSME development, and cultural preservation efforts. Increased household income, increasing employment opportunities, and the development of the creative economy are indicators that the growth of Community-Based Tourism (CBT)-based tourism villages has had a significant positive impact on the local economy. Therefore, the Kembang Kuning tourism village has become an effective means to strengthen the regional economy and encourage inclusive and long-term growth in the tourism industry.